Effect of Incisional Negative Pressure Wound Therapy vs Standard Wound Dressing on the Development of Surgical Site Infection after Spinal Surgery: A Prospective Observational Study. (18th December 2021) - Mueller, Kyle B; D'Antuono, Matthew; Patel, Nirali; Pivazyan, Gnel; Aulisi, Edward F; Evans, Karen K; Nair, M Nathan
Graphical Abstract: